(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Logical thinking organizes the teaching of students to make decisions and find the necessary information in theoretical and practical difficult situations using the acquired knowledge and skills. All this indicates that the development of logical thinking, if it is not the main task, becomes one of the most important during the student’s schooling. In this article, thoughts and comments are made about the forms, methods and means of teaching students to think logically based on innovative educational technologies.